TINGKAT KEPUASAN MAHASISWA PADA MARKETING MIX STIE SURYA NUSANTARA (STIE SN) TA 2018/2019 - Yusuf Siregar (Jurakunman (Jurnal Akuntansi dan Manajemen), 2019)
The research was intend to know the student level of satisfactory for STIE Surya Nusantara (STIE SN) marketing mix practices. The respondent of this research is the active student that registered in STIE Surya Nusantara from 2nd semester until 8th semester, sample took randomly consist of 115 students from 150 population. Data collected through questioner, questioner was developed based on seventh elements area of marketing mix of STIE SN, such as Production, Price, Place, Promotion, Participant, Process, and Physical Evidence. The result of the study, from seventh elements of marketing mix practiced by STIE SN, only fourelements rated satisfactoryby the students. The four elements are Product, Place, Participant, and Process. Key words: satisfactory, marketing mix,